Activated Carbon From Longan Seed And Pistachios Shell Prepared Via Microwave Irradiated For Dye Removal - Baharom, Siti Zawiyah (2017)
Potential of agrowastes were harnesses for preparation of activated carbon (AC) for dyes removal from aqueous solution. In this study, longan seed based activated carbon (LSAC) and pistachios shell based activated carbon (PSAC) were prepared using physiochemical activation consisting of potassium hydroxide (KOH) impregnation, CO2 gasification and microwave irradiation. The performance of the LSAC and PSAC were evaluated by conducting a batch adsorption study for methylene blue (MB) and remazol brilliant blue R (RBBR) removal. By using central composite design (CCD), the optimum preparation conditions of radiation power, radiation time and IR were determined for LSAC (440 watt, 2.0 min and IR 0.7) and PSAC (440 watt, 2.07 min and 1.0), which resulted MB removal of 77.0% and 80.9%, respectively; RBBR removal of 59.4% and 69.8%, respectively and yield of 22.1% and 21.7%, respectively. LSAC and PSAC have high surface area (>847 m2/g), pore volume (> 0.49 cm3/g) and fixed carbon content (>76%). The LSAC and PSAC have heterogeneous type pore size in mesoporous region. The effect of initial dye concentrations (25-300 mg/L), contact times (0-24 hours) and solution temperatures (30-60oC) were evaluated. The MB and RBBR adsorption by LSAC and PSAC were increased as the initial dye concentration and contact time increased. The adsorption equilibrium data for both dyes onto LSAC and PSAC were best fitted by Freundlich model. Meanwhile, the kinetic data was best represented by the pseudo first-order kinetic model. For both dyes, the adsorption of LSAC and PSAC were respectively endothermic and exothermic processes. All the adsorption processes were mainly governed by the film-diffusion controlled mechanism